Penerapan sistem enterprise resource planning: dampak terhadap kinerja keuangan perusahaan - Cornelia Endra Kristianti; Didi Achjari (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2017)
This study aims to investigate the impact of implementation of Enterprise Resource Planning (ERP) system toward Â companyâ€™s financial performance. The company's financial performance is measured by the ratio of labor productivity (LP), Return on Assets (ROA), Net Profit Margin (NPM), Account Receivable Turnover (ART), and Inventory Turnover (IT). Sample used in this study are 34 public listed companies that have implemented ERP system in the period of 2002-2013. Data were analyzed by comparing the company's financial ratios for 3 years before and after ERP implementation. The results show that productivity, receivables and inventory management are improved after ERP implementation. Unfortunately, the current research fail to show that there is an increase in companyâ€™s profitability after the implementation.